149k views
3 votes
Guys help plss:////////​

Guys help plss:////////​-example-1

1 Answer

3 votes

Answer:


f[2-f^(-1)(x)]=x

Explanation:

Given function is,

f(x) =
(x-1)/(2)

Equation form of the function will be,

y =
(x-1)/(2)

Interchange x and y,


x=(y-1)/(2)

Solve for y,

y = 2x + 1

Therefore, inverse of the function 'f' will be,


f^(-1)(x)=2x+1

Now
[2-f^(-1)(x)] = 2 - [2x + 1]

= -2x + 1

Value of
f[2-f^(-1)(x)] = f(2x + 1)

From the given function,

f(2x + 1) =
((2x+1)-1)/(2)

= x

Therefore, value of
f[2-f^(-1)(x)]=x

User JaimeJorge
by
5.5k points